N-DIMENSIONAL KALUZA-KLEIN TWO FLUID COSMOLOGICAL MODEL - PUND*, A. M.; NIMKAR, A. S. (International Journal of Mathematical Archive, 2018)
N-dimensional two fluid Kaluza-Klein space time is consider in general theory of relativity. In these models one fluid is the radiation distribution which represents the cosmic microwave background and the other fluid is the perfect fluid representing the matter content of the universe. For solving the Einstein’s field equations the relation between metric coefficients a&b and law for equation of state are used. Also, some physical and kinematical properties of the model are studied.